SUPERVISION TOWARDS IMPROVING ONLINE LEARNING AS SOON AS POSSIBLE DURING THE COVID-19 PANDEMIC - Gunawan Dwiyono; Djoko Kustono (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
The big role of school principals in supporting the improvement of the quality of education should be reviewed comprehensively and completely based on problems in the school. That since March 16, 2020 the government has called for learning to be carried out online. So, the change so quickly in the way of learning is surprising for both teachers and students, various problems arise. So that the school also began to anticipate participating in finding solutions to anticipate problems that occur in online learning. There are 3 direct policies simultaneously that we must implement in a situation of learning crisis at that time, namely social restrictions due to the COVID-19 pandemic forcing online learning, independent learning without the UN so that students can assess student competencies in the form of written tests or other more comprehensive forms of assessment, such as portfolios and assignments (group assignments, written papers, etc.), curriculum in special conditions or emergency curriculum, schools can use a curriculum that suits the learning needs of students. This situation is discussed in this paper, the efforts of Public Vocational High School 11 Malang to supervise to improve online learning that was previously completely unprepared. Suddenly, all teachers should do online learning using IT media, repairs can be made quickly and effectively during the pandemic.